A Public Transportation Renaissance in a Post-Pandemic Context - Gherman, Stefan (2023)

Sense of Belonging Among English-speaking Youth in Québec : Confronting Isolation Through Digital Community Building - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2022)
Since the onset of Covid-19, community has come to inhabit a digital medium for many of Québec’s English-speaking youth. But what does this mean in concrete terms? How is this linguistic minority using social media, and in what manner are they experiencing this digital shift? Will they want to keep having online events going forward? Our paper observes the digital behavior of young (aged 16-30) English-speaking Québecers from March 2020 until the current moment in the pandemic’s development.

The Effects of the Pandemic on the Arts & Creative Sector in Québec : How Anglophone Artists, Creators, and Performers are Faring in a Time of Adversity - Eraso, Cecilia (Youth for Youth Québec (Y4Y Québec), 2022)
The arts, entertainment, and recreation sector is infamous for being in a state of constant flux. The experience of consecutive short-term contracts and annual seasonal employment terminations is a familiar reality for many creators, producers, and performers in Québec (Jeannotte, 2021). What is unique for some Québec artists is the experience of a linguistic divide in the provincial arts sector. In 2016, English-speaking artists in the province earned less than their Francophone counterparts, on average, making a median income of “85 cents for every $1 made by Francophone artists’’ (Hill, 2020). On the national level, statistics from the 2016 Canadian Census show that Anglophone artists from Québec have a lower median income than the rest of Canadian artists. These findings are especially surprising when considering that, nationally, English-speakers in Québec represent a significant portion of Canadian artists. Anglophones in Québec account for 4.6% of all Canadian artists, despite only representing 2.8% of the Canadian labour force (Hill, 2020). The data indicate that two factors, occupation and language, are related to discrepancies in income levels in Québec.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Y4Y Québec Holds Consultation to Explore Post-Secondary Students' Experiences During Pandemic : Youth Speak Up About Ongoing Challenges Throughout the COVID-19 Pandemic in Relation to their Mental Health and Educational Experience - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Digital Outreach to Post-Secondary Students During Covid-19 - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016